Genetic variants in BDNF (rs6265 and rs11030119) and stroke susceptibility: a case-control analysis in South India - Anushree Muraleedharan Nair; Chandrasudan Ramamoorthi; Madhushri Arumugam Senthilkumar; Remasri Kanniyapillai; Praveen Kumar Chandra Sekar; Akram Husain Rehman Syed Rasheed; Subramaniyan Kannaian; Ramakrishnan Veerabathiran (Annals of Human Biology)
Background Stroke occurs when the blood supply to part of the cerebral cortex is blocked, depriving it of oxygen and glucose, leading to cell death. It is a multifactorial disorder influenced by genetic, vascular, and environmental factors.Aim This study investigated the association between two polymorphisms of the brain-derived neurotrophic factor (BDNF) gene, rs6265 and rs11030119, and stroke risk in a South Indian population.Subjects and Methods The study included 163 stroke cases and 160 healthy controls. Genomic DNA was extracted, and genotyping of rs6265 and rs11030119 polymorphisms was done using ARMS-PCR. Allelic and genotype frequencies were calculated, and odds ratios (OR) with 95% confidence intervals (CI) were determined using SPSS version 21.0.Results The rs6265 polymorphism was significantly associated with stroke risk, with the GG genotype more frequent in controls (OR 1.79, 95% CI 1.05–1.76, p = 0.01). The rs11030119 polymorphism showed a positive association, with the AA genotype more prevalent in cases (OR 2.70, 95% CI 1.34–5.44, p = 0.003).Conclusion This study suggests an association between BDNF polymorphisms (rs6265, rs11030119) and stroke risk in a South Indian population. Further research in larger populations is necessary to confirm these findings and explore the mechanisms involved.